Clinical and Epidemiological Characteristics of Opium Addiction, With Concomitant Abuse of New Psychoactive Substances - Eshankulov Rustam Mansurovich (Scholars Digest Publishing, 2023)
At the same time, according to many authors, there is currently a methodological crisis in modern Russian clinical addiction medicine. The prospects of overcoming this crisis can be judged only by separate publications devoted to the basic issues of addictology. In connection with the new "social order" associated with a significant expansion of addiction pathology, there is a need for structural changes in psychiatry and addiction medicine. According to V.D. Mendelevich, it is advisable to create an addictological service, which would be able to combine the efforts of psychiatrists, narcologists, clinical psychologists and social workers in the development of an effective strategy to counteract the spread of addictions.
Keywords: psychoactive substances, acute intoxication.